The Influence of Job Satisfaction and Psychological Well-Being On Turnover On Hospital Employees - Abduh Rahmat Amri; Ribhan Ribhan; Ayi Ahadiat (Syntax Corporation, 2022)
Health decentralization allows the Bandar Lampung City Health Office to design programs and service activities that are appropriate to local conditions. Based on data obtained from the HR department of private hospitals in Bandar Lampung City, the number of employees in private hospitals is 326 people and therate turnover reaches more than 10% per year. The purpose of this study was to determine the relationship between psychological well-being and job satisfaction with therate turnover at the Bandar Lampung City Private Hospital. The results of the study found that Job Satisfaction and Psychological Wellbeing had a simultaneous effect on employee turnover. This is evidenced by the statistical results of F count 18,539 > F table value of 3.07, with a significance of 0.00; Job satisfaction has a significant effect on employee turnover with a t-table value of 1.657 and a t-count value of 3.437; Psychological Wellbeing has a significant effect on employee turnover, with t count of 6.051 which means t count > t table (6.051> 1.657) and sig 0.00 < 0.05.